Using Drawing Games to Enhance Second Language Vocabulary Knowledge in Thai EFL Learners - Teemueangsai, Sirathee; Sukying, Apisak; Min, Changyong (Theory and practice in language studies, 2025)
This study examines the effects of drawing games on L2 vocabulary knowledge among Thai EFL learners. The study used a quasi-experimental design with 40 ninth-grade students from two intact classes assigned to an experimental group (drawing game activities) and a control group (traditional instruction). Vocabulary knowledge was assessed with four test types: passive recognition, active recognition, passive recall, and active recall. Pre-, post- and delayed post-test results were used to assess the acquisition and retention of vocabulary knowledge. The findings indicated that the experimental group significantly outperformed the control group in all test types, with the greatest improvements in recognition-based tasks. Post-hoc analyses confirmed a difficulty hierarchy for the four types of vocabulary knowledge: active recall, passive recall, active recognition, and passive recognition. Additionally, the delayed post-test results further indicated better long-term retention of drawing in the experimental group, confirming the lasting effect of drawing-based training. Additionally, student feedback revealed positive perceptions of drawing games, particularly regarding engagement, enjoyment, and effectiveness in form-meaning mapping. Together, the present study supplies empirical support for the use of drawing games as a pedagogical instrument for vocabulary learning in EFL settings. The results support the use of visual, interactive tasks in language education to enhance learners’ vocabulary performance, motivation, and long-term retention.